210 likes | 308 Views
Pythagorean Theorem. a = altitude b = base c = hypotenuse. c. a. b. a = altitude b = base c = hypotenuse. a = altitude b = base c = hypotenuse. a = altitude b = base c = hypotenuse. a = altitude b = base c = hypotenuse. Area of each rectangle is a b. a = altitude b = base
E N D
a = altitude b = base c = hypotenuse c a b
a = altitude b = base c = hypotenuse
a = altitude b = base c = hypotenuse
a = altitude b = base c = hypotenuse
a = altitude b = base c = hypotenuse Area of each rectangle is ab
a = altitude b = base c = hypotenuse Sum of areas = 2ab
a = altitude b = base c = hypotenuse
a = altitude b = base c = hypotenuse Sum of areas = 2ab
a = altitude b = base c = hypotenuse Sum of areas = 2ab
a = altitude b = base c = hypotenuse Sum of areas = 2ab
a = altitude b = base c = hypotenuse Sum of areas = 2ab
a = altitude b = base c = hypotenuse Sum of areas = 2ab
a = altitude b = base c = hypotenuse Sum of areas = 2ab
a = altitude b = base c = hypotenuse Sum of areas = 2ab
a = altitude b = base c = hypotenuse a - b Sum of areas = 2ab
a = altitude b = base c = hypotenuse a - b Sum of areas = 2ab Area = (a - b)2
a = altitude b = base c = hypotenuse a - b Sum of areas = 2ab Area = (a - b)2 Total area = c2
a = altitude b = base c = hypotenuse Sum of areas = 2ab Area = (a - b)2 Total area = c2 c2 = (a - b)2 + 2ab
a = altitude b = base c = hypotenuse Area = (a - b)2 Total area = c2 c2 = (a - b)2 + 2ab c2 = a2 - 2ab + b2 + 2ab c2 = a2 + b2 Sum of areas = 2ab